On-demand trust evaluation - COGHLAN, BRIAN ARTHUR; O'CALLAGHAN, DAVID (IEEE, 2006)
Security is a critical factor in interoperability of grid middleware. There is an opportunity to automate the trust evaluation and accreditation process for grid certification authorities to allow continuous evaluation of their policies and practices. To assess the feasibility and usefulness of automatic evaluation of trust in CAs a trust evaluation system has been designed and a prototype implemented. The service will evaluate a CA based on its published policies and observed practices with respect to a set of rules based on the requirements from an authentication profile. Development and testing are ongoing and we hope to deploy a pilot system shortly.
7th IEEE/ACM International Conference on Grid Computing
7th IEEE/ACM International Conference on Grid Computing (Grid 2006)
Keywords: grid computing